DYSPHAGIA IN CHILDREN WITH CEREBRAL PALSY AND THE ROLE OF FIBEROPTIC ENDOSCOPIC EVALUATION OF SWALLOWING (FEES): A REVIEW - Joshua Runtuwene (JURNAL KEPERAWATAN, 2023)
Background: Cerebral palsy (CP) is a neurological disorder that affects muscle control and coordination, often resulting in various physical and developmental challenges. Dysphagia poses a common challenge in children diagnosed with cerebral palsy, significantly impacting their ability to eat and swallow. The mechanisms of dysphagia in children with cerebral palsy can be multifactorial and involve several factors, including oral motor dysfunction, decreased muscle tone, gastroesophageal reflux, delayed or disorganized swallowing reflexes, sensory issues, and structural abnormalities. Accurate assessment of dysphagia is vital for effective management. Aim: This comprehensive review aims to provide a thorough explanation of dysphagia in pediatric CP, with a particular focus on the application of Fiberoptic Endoscopic Evaluation of Swallowing (FEES) as an evaluative tool. Method: A comprehensive search strategy was utilized to locate relevant studies from databases including PubMed Medline, Cochrane, Embase, Proquest, dan Scopus. Results: In cerebral palsy-related dysphagia, disruptions in muscle coordination and control during swallowing can result in significant complications. Early detection and intervention are vital to minimize adverse outcomes. FEES is a safe outpatient procedure used to assess swallowing in this condition, with abnormal findings including delayed swallow initiation, reduced tongue control and bolus manipulation, impaired velopharyngeal closure, reduced laryngeal elevation and closure, decreased epiglottic movement, pharyngeal residue, and signs of penetration or aspiration. Conclusion: Overall, FEES offers valuable insights into the swallowing function of these children and helps guide appropriate treatment interventions Keywords: dysphagia; FEES; children; cerebral palsy